2022
DOI: 10.3390/su142416666
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Production of Thiosulfate from Organic and Inorganic Sulfur Substrates for Application to Gold Leaching

Abstract: Gold mining and processing is an activity with large environmental impact due to the low concentration of gold in ore deposits and chemical resistance to most chemicals. Over 75% of gold is leached from ores using cyanide, however less toxic lixiviants have been proposed in the literature. Thiosulfate is one of these alternative reagents, but high reagent consumption has slowed acceptance in mining operations. Reducing the cost and impact of thiosulfate production is a way to reduce the cost of reagent consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…As a result of these microbial activities, thiosulfate (S 2 O 3 2− ) is produced as a generally considered undesirable byproduct [26,27]. Biologically produced thiosulfate has been recently used in leaching processes for the recovery of gold and silver [28][29][30]. In the study conducted by McNeice et al [30], they reported gold extraction efficiencies spanning a range from 20 to 60%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of these microbial activities, thiosulfate (S 2 O 3 2− ) is produced as a generally considered undesirable byproduct [26,27]. Biologically produced thiosulfate has been recently used in leaching processes for the recovery of gold and silver [28][29][30]. In the study conducted by McNeice et al [30], they reported gold extraction efficiencies spanning a range from 20 to 60%.…”
Section: Introductionmentioning
confidence: 99%
“…Biologically produced thiosulfate has been recently used in leaching processes for the recovery of gold and silver [28][29][30]. In the study conducted by McNeice et al [30], they reported gold extraction efficiencies spanning a range from 20 to 60%. This was achieved through the utilization of biogenic thiosulfate, following the production of approximately 400 mg L −1 of biogenic thiosulfate with the aid of sodium sulfide (Na 2 S) (chemical source) in conjunction with M. sulfidovorans (DSMZ 11578).…”
Section: Introductionmentioning
confidence: 99%